ä½¿ç”¨æ¨¡ä»¿æ•™å¦æ³•æé«˜å¦ç”Ÿå¯¹æ±‰è¯å››å£°çš„æŽŒæ¡èƒ½åŠ› - Pujiati, Sri; ., Ina; ., Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
æ‘˜è¦ï¼šæœ¬æ–‡çš„ä¸»è¦ç›®çš„æ˜¯äº†è§£æ¨¡ä»¿æ•™å¦æ³•å¯¹å¦ç”Ÿå¦ä¹ æ±‰è¯å››å£°çš„æ•ˆæžœï¼Œæ˜¯å¦æœ‰æ•ˆæé«˜å¦ç”Ÿçš„æ±‰è¯å››å£°æŽŒæ¡èƒ½åŠ›ã€‚ç ”ç©¶å¯¹è±¡æ˜¯Taruna Bumi Khatulistiwaé«˜ä¸ä¸€å¹´çº§ç¤¾ä¼šä¸€ççš„å¦ç”Ÿï¼Œå…±æœ‰30åå¦ç”Ÿï¼ˆç”·ç”Ÿ12åï¼›å¥³ç”Ÿ18åï¼‰ã€‚ç ”ç©¶æ–¹æ³•æ˜¯å®žéªŒæ³•å’Œæµ‹è¯•æ³•ã€‚æ ¹æ®æœ¬æ–‡çš„æ•™å¦å®žéªŒä»¥åŠå‰åŽæµ‹çš„ç»Ÿè®¡ä¸Žåˆ†æžï¼Œç¬”è€…äº†è§£åˆ°æ¨¡ä»¿æ•™å¦æ³•èƒ½æœ‰æ•ˆåœ°æé«˜å¦ç”ŸæŽŒæ¡æ±‰è¯å››å£°çš„èƒ½åŠ›ã€‚ä»Žè€Œå–å¾— ç›¸å½“å¥½çš„æ•™å¦æ•ˆæžœã€‚ å…³é”®è¯ï¼šå£°è°ƒï¼›å››å£°ï¼›æ¨¡ä»¿æ•™å¦æ³• Abstractï¼šThe purpose of this research is to know the effect of imitating teaching method for the student to learn Mandarin 4 tones, to know that if it can increase the students ability in mastering Mandarin 4 tones. The object of this research are students of the first grade of Senior High School Taruna Bumi Khatulistiwa, social class one, with total students were 30 students (12 male; 18 female). The research method are practice and aÂ  method of test . Based on analysis of the teaching learning process in the classroom and the result in pre-test and post-test, the writer gets that result imitating teaching method is effective in improving the ability of the students in mastering Mandarin 4 tones. Thus, the students have got a good improvement during learning process. Keywords:Â  Tone; Four Tones; Imitating Teaching Method